Selection, Identification and Optimization of the Growth Water Probiotic Consortium of Mangrove Ecosystems as Bioremediation and Biocontrol in Shrimp Ponds - Wilis Ari Setyati; Erni - Martani; Triyanto - -; Subagiyo - -; Muhammad - Zainuddin (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Shrimp aquaculture is an activity that potentially generates organic waste. The accumulation of organic matter is becoming one of the main factors causing the emergence of disease. Problem-solving approach that is most effective is through bioremediation. The aims of this study were to select, identify and cultivate bacteria from mangrove sediments from Cilacap, Rembang and Banyuwangi which potentially as probiotic consortium of bioremediation activity and biocontrol. The results showed that total of 45 isolates (proteolytic), 35 isolates (amylolytic), 35 isolates (lipolytic), and 18 isolates (cellulolytic). There were 59 bacterial isolates had antibacterial activity of vibrio (V. harveyi, V. alginolyticus, V. vulnificus and V. anguilarum). Based on the identification of 16 S-rRNA genes, 4 isolates showed that the C2 isolate was identified as Bacillus subtilis, C11 isolate was identified as Bacillus firmus, C13 and C14 isolates were identified as B. Flexus. This study concluded that cultivation of Bacillus subtilis C2 optimum at 2% molase and yeast extract 0.5% at pH 8 and 30 0C. Bacillus firmus C11 optimum at 2% molase and yeast extract 0.5% at pH 8 and 30 0C. Bacillus flexus C13 optimum at 2% glucose and yeast extract 0.5% at pH 8 and 30 0C. Bacillus flexus C14 optimum at 4% molase and yeast extract 0.25% at pH 8 and 30 0C. The result of culture applications of 4 isolates showed an effect of increasing shrimp weight by 141, 9% compared by the control.Keywords: sediment, mangrove, bioremediation, biocontrol